Answer:
B
Explanation:
isolate the factor with x in it
subtract k from both sides
a(x - h)² = y - k ( divide both sides by a )
(x - h)² = ( take the square root of both sides )
x - h = ±
finally add h to both sides
x = ± + h → B
B ±sqrt((y-k)/a ) + h= x
y=a(x-h)^2+k
Subtract k from each side
y-k = a(x-h)^2+k-k
y-k = a(x-h)^2
Divide by a
(y-k)/a = a(x-h)^2/a
(y-k)/a = (x-h)^2
Take the square root of each side
±sqrt((y-k)/a )= sqrt((x-h)^2)
±sqrt((y-k)/a )= (x-h)
Add h to each side
±sqrt((y-k)/a ) + h= (x-h+h)
±sqrt((y-k)/a ) + h= x
5.8m questions
7.5m answers